Economic value of tropical inland freshwater shallow lakes: Lesson from Lake Malombe, Malawi. (20th October 2021) - Makwinja, Rodgers; Mengistou, Seyoum; Kaunda, Emmanuel; Alamirew, Tena
Abstract: Freshwater lakes provide critical ecosystem services (ESs) to local and global communities. However, many of these lakes are under serious threat from degradation, over‐exploitation and pollution instigated by unsustainable use and a lack of practical management approaches. Under such conditions, it is critical to quantify the ESs of these lakes and uncover factors affecting local population participation in the conservation. The current study aims to fill this research gap by employing data collection techniques such as household surveys, focus group discussion, field observation, key informant interviews, consultative meetings and a meta‐analytical approach. Lake Malombe has been selected to depict the African freshwater ecosystems' scenarios. The findings show that 97.74% of the households depend on the lake ESs. The ESs contribute US$124.36 million/year—about 1.97% of Malawi's GDP and US$1943.08/household/year. Factors such as literacy level, household level of income, age of household head, gender of household and household experiences food shortages significantly ( p  < 0.05) influenced participation level. The study recommends integrating the economic incentive model into the local policy framework. For example, promoting ecotourism, agroforestry and integrated fish farming can provide economic incentives, reduce direct dependency and increase local participation in conservation. Résumé: Les lacs d'eau douce assurent des services écosystémiques (SE) essentiels aux populations au niveau local et mondial. Cependant, bon nombre de ces lacs sont gravement menacés par la dégradation, la surexploitation et la pollution provoquées par une utilisation non viable et des lacunes en matière d'approches pratiques de gestion. Dans de telles conditions, il est essentiel de quantifier les SE de ces lacs et d'identifier les facteurs affectant la participation de la population locale à la conservation. La présente étude vise à combler ces lacunes en matière de recherche à l'aide de techniques de collecte de données telles que des enquêtes auprès des ménages, des discussions de groupe, des observations sur le terrain, des entretiens avec des informateurs clés, des réunions consultatives et une approche méta‐analytique. Le lac Malombe a été choisi pour représenter les scénarios des écosystèmes d'eau douce africains. Les résultats montrent que 97, 74 % des ménages dépendent des SE du lac. La contribution des SE se traduit par un montant de 124, 36 millions de dollars US par an, soit environ 1, 97 % du PIB du Malawi et un montant de 1 943, 08 de dollars US par ménage par an. Des facteurs tels que le niveau d'alphabétisation (NA), le niveau de revenu du ménage (NRM), l'âge du chef de ménage (ACM), le sexe du chef de ménage (SCM) et les ménages confrontés à une pénurie de denrées alimentaires (MCPDA) influencent le niveau de participation de manière significative (p<0, 05). L'étude recommande l'intégration du modèle d'incitation économique au cadre de la politique locale. P. ex., la promotion de l'écotourisme, de l'agroforesterie et de la pisciculture intégrée peut déboucher sur des incitations économiques, réduire la dépendance directe et accroître la participation des populations locales à la conservation.